Are consumers in Slovenia concerned about the mountain quality food - Majkovič, Darja; Borec , Andreja (Journal for Geography, 2010)
Recently, several studies on Mountain quality food products (further referred to as MQFP) emerged EU wide, especially after the EU charter of MQFP was established. In Slovenia, the first studies on MQFP where implemented in the frame of the EU FP6 EuroMarc project, started in 2007. After the project scope, the importance of MQFP is much more extensive then only according to purchase and consumer perceptions, thus the developing of mountain food products is also the developing of mountain areas and therefore part of broader rural development issues. In the paper, the first consumer analyses are presented, with the aim to find out whether consumers are sensitive to such products at all and to find out whether there exist some positive synergies between consumers and area of origin. The consumer analyses were carried out on the basis of questionnaires, and the data is presented with the descriptive statistic. The results show that consumers have in general a very positive perception of MQFP, although they do not know what exactly the characteristics of MQFP should be. As regards the synergies between the area of origin and the purchasing of MQFP, the results differ according to the area the respondents come from (e.g. mountain, non-mountain areas).